Genetic Polymorphism at Acaca Locus and Its Relationship With Productive Performances in Ettawa Crossbred Goat - Sucik Maylinda; Tri Eko Susilorini; Puguh Surjowardojo (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2015)
Research with aim to estimate genetic polymorphism at ACACA (Acetyl-coenzyme A carboxylase ) locus in Ettawa Crossbred goat wan its relationship with production traits was done at goat population in Batu, Lawang and Ampel Gading. 46 female goats were taken it’s blood sample to isolate the DNA and continue with PCR (Polymerase Chain Reaction) and RFLP (Restricted Fragment Length Polymorphism). PCR was used to amplify ACACA gene fragment in intron 3’ about 200 bp with primer F : 5’ – AGT GTA GAA GGG ACA GCC CAG C – 3’ and R : 5’ – GTG GAA TGA CAC ATG GAG AGG G – 3’; RFLP was used to test mutation of that fragment in particular place (point) using restriction enzyme RSA1. Variables were alelles and genotypes composition in population, milk and fat content, and birth weight of kid. Result showed that (a) genetic polymorphism at locus ACACA in three location was high that is 44,22 %, with allele frequency of G (p) = 33 % and allele T (q) = 67 %; (b) no relationship between the high polymorphism with productive performance of goat in fat and protein content, and birth weight of kid. It was concluded that in goat population there was a high polymorphism at ACACA gene, and that polymorphism was not related to production.